Application of Benford's Law in Payment Systems Auditing - Žgela, Mario; Krakar, Zdravko (Journal of Information and Organizational Sciences, 2009)
Information systems auditing activities are mandatory in today business environments. There are numerous useful methods that can be conducted in such audits. One of contemporary methods is application of so-called Benford's Law. In this paper we examine ways of application of this law in investigation of certain number set with aim to make a conclusion if number set conforms to Benford's Law. As an examination target we used foreign payment system messages which are issued between foreign and domestic business entities i.e. commercial and central banks. We chose sample of 1.745.311 transactions and conducted examination for first, second and first two digits. We examine certain data subsets, created according to certain payment types, and investigate how Benford’s Law tests can be used in auditing. We also compare practical usefulness and note differences between various conformity tests in auditing environment. Results we achieved prove adequate potential of this law in audit practice.